Nueva Ley Orgánica y el gobierno corporativo. Mayor apertura en PEMEX. - Suárez Guevara, Sergio (Dimensión Económica, 2010)
The debate that took place in the Senate on reforming the country’s Energy or PEMEX proposed by the Executive, leads us to write some comments to show that behind a wealth of concepts, emphasizing the corporate governance, which seeks to hide the continuation of a process of opening unconstitutional that has been applied on PEMEX for two and a half decades, with dark interest of promoting the privatization of strategic public company, giving a hint of Private enterprise culture to its social function and operation.